Potential of Phosphorus Pollution in The Soil of The Northern Gaza Strip, Palestine - Mazen Solaiman Hamada; Adnan Aish; Mai Shahwan (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2011)
The damage and negative consequences of the Israeli Cast Lead on Gaza in the period between December 2008 - January 2009 is not only limited to the number of martyrs and wounded people, the destruction of houses and the infrastructure, but it also reached the environment. This paper investigates the occurrence of phosphorus (P) in the soil of the northern gover-norate of the Gaza Strip which has been shaped as a result of the heavily bombing of white phosphorus on Gaza during the war. We have measured soil Phosphorus concentrations in three different areas; agricultural, non-agricultural and urban areas. The obtained Olsen P values in most of the soil samples were ranked very high. The maximum value of phosphorous determined in agricultural areas was about 110.9 mg/ kg, in the non-agricultural areas adjacent to boarders 63.3 mg/ kg, and in urban areas 85.2 mg/ kg. The results show that the potential of phosphorus in the northern of the Gaza Strip is becoming higher than the allowed Olsen P values. Keywords: Phosphorus, Soil pollution, Olsen P, Gaza Strip